1983
DOI: 10.1172/jci111082
|View full text |Cite
|
Sign up to set email alerts
|

Restriction fragment length polymorphism associated with the pro alpha 2(I) gene of human type I procollagen. Application to a family with an autosomal dominant form of osteogenesis imperfecta.

Abstract: A B S T R A C T One cloned complementary DNA and one genomnic subclone were used to detect restriction fragment length polymorphism associated with the proa2(I) gene for human type I procollagen. The restriction fragments obtained from examination of 30-122 chromosomes confirmed previous indications that the proa2(I) gene is found in a single copy in the human haploid genome. One highly polymorphic site was detected with EcoRI in the 5'-half of the gene. The restriction site polymorphism at the site had an all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

1986
1986
2009
2009

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(23 citation statements)
references
References 28 publications
1
22
0
Order By: Relevance
“…This approach enabled us to focus attention on only one class of constituent chains of type I collagen. In this report we describe studies of type I collagen synthesized by cells cultured from one unaffected and two affected members of this pedigree (26). The affected members are heterozygous for a mutation in the proa2(I) gene that produces a shortened proa2(I) chain, thus confirming linkage in this family.…”
Section: Introductionmentioning
confidence: 55%
See 3 more Smart Citations
“…This approach enabled us to focus attention on only one class of constituent chains of type I collagen. In this report we describe studies of type I collagen synthesized by cells cultured from one unaffected and two affected members of this pedigree (26). The affected members are heterozygous for a mutation in the proa2(I) gene that produces a shortened proa2(I) chain, thus confirming linkage in this family.…”
Section: Introductionmentioning
confidence: 55%
“…Thus, the slower migrating population of al(I) was overmodified amino-terminal to the a l(I)CB7 domain. These findings contained an apparent paradox: although the genetic linkage data (26) indicated that the mutation should be in an a2(I) chain, the evident structural abnormality in type I collagen was overmodification of the amino-terminal half of some intracellular al(I) chains produced by the OI cells. Because Steinmann et al (12) have demonstrated that a mutation of a 1(I) could cause overmodification in all three constituent achains in a molecule at residues amino-terminal to the mutation, we hypothesized that a mutation in the middle ofan a2(I) chain might also cause excessive posttranslational modification aminoterminal to its location in all chains in such a molecule but that because a2(I) normally is more modified than a 1(I), overmodification in a2(I) might be more difficult to detect.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The fragments at Sites 1 and 2 are detected with a pro-~2(I) eDNA probe, but the restriction map of the COL1A2 gene does not contain the 7.4 kb HindlII and 3.0 kb PstI fragments characteristic of Site I nor the 4.6 kb HindllI and 5.2 kb PstI fragments characteristic of Site 2 [15,16,17]. COL1A2 genomic clones that span the same region of the gene as does the eDNA were used to probe samples where the eDNA probe had detected length polymorphisms at Sites 1 or 2 (Fig.…”
Section: Resultsmentioning
confidence: 99%